Dinamika Interaksi Antar Umat Beragama di Ledda Sujono: Dialog Keberagamaan - Lestari, Bunga; Nasution, Abdul Gani Jamora; Ramadhani, Cinta; Hidayat, Muhammad Taufik; Nasution, Pebrijah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to assess the level of tolerance between Muslims, Catholic Christians and Protestants on Jalan Letda Sujono, a sub-district in Medan City, North Sumatra, Indonesia. The main focus of research is interactions between groups and their impact on social harmony, with analysis of conflict and differences in religious views. The method uses a qualitative approach with literature study, showing that harmony between religious communities is maintained through personal and communal tolerance. The Medan Tembung Village community emphasizes dialogue, education and cooperation as the key to maintaining harmony, with policy recommendations to increase tolerance in the area. This research illustrates the harmonious balance on Jalan Letda Sujono and underlines the importance of respecting diversity as cultural richness, with Medan Tembung Village as an example of a harmonious and peaceful environment through an attitude of tolerance and harmony.